2014
DOI: 10.1108/pijpsm-07-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

The potential for violence in arrests of persons with mental illness

Abstract: Purpose-The purpose of this paper is to determine whether police use of force and suspect resistance are more likely to occur in arrest encounters involving suspects with mental health problems. Design/methodology/approach-The study uses data from interviews with 942 individuals recently arrested by officers in more than a dozen different police departments in Maricopa County, Arizona in 2010. Both logistic and ordinal regression analyses are used to predict two models of suspect resistance (resistance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
5
24
0
Order By: Relevance
“…Situational characteristics. In line with previous research (Hickman et al, 2008;Mulvey & White, 2014;Paoline & Terrill, 2004, 2007, the most robust predictors of police use of force were at the situational level. The analyses found significant positive relationships between non-weapon force and numerous features of the encounter, including suspect proximity to an offense (EXP ( Precinct-level controls.…”
Section: Multivariate Analysissupporting
confidence: 90%
“…Situational characteristics. In line with previous research (Hickman et al, 2008;Mulvey & White, 2014;Paoline & Terrill, 2004, 2007, the most robust predictors of police use of force were at the situational level. The analyses found significant positive relationships between non-weapon force and numerous features of the encounter, including suspect proximity to an offense (EXP ( Precinct-level controls.…”
Section: Multivariate Analysissupporting
confidence: 90%
“…Moreover, policing scholars have expressed particular interest in research that can adequately control for potential contributing factors (e.g., citizen resistance and drug-alcohol influence), beyond mental illness, when assessing citizen injuries (Kerr et al, 2010). Further, the limited research thus far has been unable to consistently demonstrate whether officers are more punitive and aggressive, or more empathetic, toward PMI (Mulvey & White, 2014;Novak & Engel, 2005).…”
mentioning
confidence: 99%
“…There is also a greater risk for use of force when policing the deinstitutionalized mentally ill (Mulvey and White, 2014). Someone with an illness could see an officer as a threat in himself and react negatively, or the police might not understand that there is an illness present and react negatively themselves.…”
Section: Police Interaction With the Mentally Illmentioning
confidence: 99%
“…Gur (2010) stated that the first few seconds of interaction between an officer and an individual with mental illness can determine how that interaction will end, either with de-escalation, exacerbation, or violence. Additionally, Mulvey and White (2014) found that "…individuals with a current mental health problem were nearly three times more likely to resist during the current arrest" (pg. 410-411) and while they also found that officers may be more likely to be understanding of certain aggressive or disruptive behaviors, there is a limit, and if that limit is reached, the officer might exacerbate their own response to become more forceful or coercive (2014).…”
Section: Police Interaction With the Mentally Illmentioning
confidence: 99%